Idle Capital and Long-Run Productivity - Carl-Johan Dalgaard (University of Copenhagen, Economic Policy Research Unit (EPRU), 2002)
In the present paper the joint determination of long-run income per worker and capital utilization is studied. It is shown that comparatively low (optimal) rates of capital utilization may arise in poor economies in response to weak underlying structural characteristics. Moreover, the quantitative implications of variable capital utilization are also explored. It is demonstrated that adding endogenous capital utilization to the Solow model implies a rate of convergence in line with empirical estimates, and, that controlling for capital utilization leads to interesting modifications of the results stemming from oft-cited exercises in cross-country growth and levels accounting.
Keywords: 330; Kapazitätsauslastung; Produktivität; Theorie